(3efjI GdQGVi HQSGFd GdbGVi aj GdefTCJs - (3CHh GdaVd CMeO Hf eMeO GdejOGfis; (3GdejOGfj , CHh GdaVd CMeO Hf eMeO Hf CMeO Hf EHQGgje GdejOGfj GdfjSCHhQj,J (B518 (3g` s ((3eMeO Hf CHj GdaVd GdUGFZi s)
(3ChdgG (B:s
(3gPg ZQGFH GdCdaGX EfJbjJgG eeG YfOi ef cdGe GdbGVi GdGROi hLYdJgG YTQI QSGFd ai YTQI CfhGY s
(3BNQgG (B:s
(3aUd ai eG dOhGe GHbGg Gddg ai cPG eG UOMJ MeGeI hSaMJ ZeGeI heG bQG GdGQV bQGQgG eG JfGhH GdUHGM hGdeSGA hGfWHb Ydi GdGQV GdSeGA Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdYGTQs
(3GdbGVi gh CHj CMeO efUhQ Hf eMeO GdCROi GdgQhis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeYGQa GdYGeIs